2013
DOI: 10.3390/su5072944
|View full text |Cite
|
Sign up to set email alerts
|

Transferring the Integrated Pollution Prevention and Control (IPPC) Approach and Best Available Techniques (BAT) Concepts to Egypt, Tunisia and Morocco

Abstract: Abstract:The principles introduced by the Directive Concerning Integrated Pollution Prevention and Control (IPPC) (currently known as the Industrial Emissions Directive (2010/75/EU)) are innovative and have raised interests in the framework of the literature debate on environmental regulation. Many articles describe and analyze the application of the Directive in European countries, but only a few articles focus on how the interest for the Directive's principles, including the integrated approach, have reached… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…OHS: Champoux and Brun, 2003;Cherniack andLahiri, 2010 EE: Chan, 2008;Côté et al, 2006;Daddi et al, 2013;Gunningham and Sinclair, 1997;Massoud et al, 2010;Matus et al, 2012;Mittal et al, 2013;Mittal and Sangwan, 2014;Shi et al, 2008;Siaminwe et al, 2005;Silva Lopes et al, 2013;Vieira and Amaral, 2015;Zilahy, 2004EnEff: Fleiter et al, 2012bNagesha and Balachandra, 2006;Reddy and Shrestha, 1998;Sardianou, 2008;Schleich, 2009;Schleich and Gruber, 2008;Sorrell et al, 2000;Trianni and Cagno, 2012;Walsh and Thornley, 2012;Worrell and Price, 2001 This operation allowed us to point out several elements of novelty. First, we found that many barriers could also apply to areas other than those cited.…”
Section: Pay Back Timementioning
confidence: 99%
See 1 more Smart Citation
“…OHS: Champoux and Brun, 2003;Cherniack andLahiri, 2010 EE: Chan, 2008;Côté et al, 2006;Daddi et al, 2013;Gunningham and Sinclair, 1997;Massoud et al, 2010;Matus et al, 2012;Mittal et al, 2013;Mittal and Sangwan, 2014;Shi et al, 2008;Siaminwe et al, 2005;Silva Lopes et al, 2013;Vieira and Amaral, 2015;Zilahy, 2004EnEff: Fleiter et al, 2012bNagesha and Balachandra, 2006;Reddy and Shrestha, 1998;Sardianou, 2008;Schleich, 2009;Schleich and Gruber, 2008;Sorrell et al, 2000;Trianni and Cagno, 2012;Walsh and Thornley, 2012;Worrell and Price, 2001 This operation allowed us to point out several elements of novelty. First, we found that many barriers could also apply to areas other than those cited.…”
Section: Pay Back Timementioning
confidence: 99%
“…OHS: Champoux and Brun, 2003;Cherniack and Lahiri, 2010;Hasle andLimborg, 2006 EE: Chan, 2008;Daddi et al, 2013;Doniec et al, 2002;Martín-Peña et al, 2014;Massoud et al, 2010;Matus et al, 2012;Ministerie Van Vrom, 2004;Mittal and Sangwan, 2014;Murillo-Luna et al, 2011;Shi et al, 2008;Silva Lopes et al, 2013;Studer et al, 2006;Vernon et al, 2003;Vieira and Amaral, 2015;Zhang et al, 2009;Zilahy, 2004EnEff: Cagno et al, 2013Fleiter et al, 2012b;Nagesha and Balachandra, 2006;Reddy and Shrestha, 1998…”
Section: Ee: Ministerie Vanmentioning
confidence: 99%
“…And the final gate both for CSF and barriers is concerned with the economic dimension. In this way, financial aspects that were pointed out in the literature by Dieleman (2007), Daddi et al (2013) and Dobes (2013), as a major obstacle to applying CP, appears not to be such a significant barrier in the opinion of the participants. In this study, the fourth component of the barriers PCA was comprised by difficulty in recognizing the economic benefits (B5), and lack of financial resources (B6).…”
Section: Discussionmentioning
confidence: 95%
“…a polyphagous insect and can attack various economical crops throughout the year (EPPO, 2014). Mainly, it results in economic losses to a broad range of ornamental, industrial and vegetable crops in Egypt (Daddi et al;. When synthetic insecticides have been used continuously over the year; insect resistance was the hatful result (Abo-El-Ghar et al, 1986;El-Baramawy et al 1991).…”
Section: Introductionmentioning
confidence: 99%